Low temperature carbon dioxide injection in high temperature oil reservoirs - Hamdi, Z. (Society of Petroleum Engineers, 2014)
Carbon dioxide injection has been used as a successful tertiary recovery method for the past decades. The main advantage of CO2 is its miscibility with the crude oil which can lead to higher recovery. Large quantity of CO2 exploration is often explored as gas or supercritical phase; but, low temperature CO2 is produced in some downstream facilities such as cryogenic separation units. This low temperature CO2 opens a novel opportunity to evaluate the potential of low temperature CO2 injection for both storage and enhanced oil recovery methods. In this study, a non-isothermal compositional simulation was conducted using a commercial simulator to examine the performance of low temperature CO2 injection process in a high temperature reservoir. The results showed that, after 24 years of production, 8.73 increase of total oil recovery by liquid CO2 is expected in comparison with supercritical CO2 injection in isothermal mode (200 Â°F). It also shows the high storage capability of CO2 in this method. The storage of CO2 increased by 11.2 in compare with isothermal mode. The results of this study proved a significant advantage for low temperature CO2 injection to improve oil recovery as well as storage capability that can be implemented in the field. Copyright Â© 2014, International Petroleum Technology Conference.